Stillbirth and associated perinatal outcomes in obstetric cholestasis: a systematic review and meta-analysis of observational studies. (July 2019) - Mohan, Manoj; Antonios, Antoniou; Konje, Justin; Lindow, Stephen; Ahmed Syed, Mohamed; Akobeng, Anthony
Abstract: Background: Obstetric cholestasis is a condition occurring in pregnancy with suspected adverse perinatal outcomes. Stillbirth is a significant adverse event associated with obstetric cholestasis and considered for intervention in pregnancy. Objectives: There are multiple studies with epidemiological data with regards to the outcomes of obstetric cholestasis. Our hypothesis is to the test the association of stillbirth and related outcomes in obstetric cholestasis. Search Strategy & Selection criteria: Two independent reviewers did independent searches and selection with a standardized design as outlined in the PRISMA statement. Analysis: The retrieved relevant literature was subjected to a rigorous quality assessment and followed by standardized interpretable results. Results: The pooled estimate in this study showed that there was no significant difference in the stillbirth rates in the obstetric (OC) population when compared to the non-obstetric cholestasis (reference) population. However, there was an increased risk of preterm birth in the OC population compared to the reference population; however, the cesarean section and induction of labor results were directly related. Discussion: This study provides an epidemiological data related to the perinatal outcomes associated with obstetric cholestasis, specifically stillbirth. This result is likely to produce a benchmark for current evidence-based practice and to assist future research in understanding the implication of associated stillbirth risk and related outcomes with OC.